Microbiological evaluation of sugarcane juice sold at street stands and juice handling conditions in São Carlos, São Paulo, Brazil - Oliveira Aline Cristine Garcia; Seixas Antonio Sergio Spano; Sousa Cristina Paiva; Souza Clovis Wesley Oliveira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2006)
Fresh sugarcane juice is sold by street vendors without any heat treatment in São Carlos, São Paulo, Brazil. Twenty-four samples of point-of-sale juice were tested by standard methods to determine heterotrophic bacteria, total and thermo-tolerant coliform counts, Salmonella, and parasites in the juice. 25% of samples showed poor sanitary conditions, with thermo-tolerant coliform levels higher than allowed by Brazilian standards. Salmonella spp. and parasites were absent in all samples. Thermo-tolerant coliforms were detected on the hands of 37% of juice handlers, and heterotrophic bacterial counts reached 2.0 x 10³ cfu/per hand. Escherichia coli was detected in one hand sample, and no Salmonella spp. was detected. Screening questionnaires were used to interview the vendors, and 62% of interviewees were either unfamiliar with or failed to adopt adequate hygiene for food handling.